Pyramidal Shikhara of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the samvarna variety of pyramidal shikhara of the Mahanaleshwar temple. Each of the small aedicules is composed of small discs that descend like a pyramid. Since the aedicules have bell-like finials, the type of shikhara is known as ghanta samvarna.